An amphoteric and hydrogen-bond-rich artificial α-amino acid for highly durable aqueous redox flow batteries - Pengbo Zhang; Yuzhu Liu; Jie Wei; Zuoao Wu; Xinmei Song; Guochun Ding; Huaizhu Wang; Junchuan Liang; Zuoxiu Tie; Zhong Jin (Nature Communications)
Abstract Aqueous organic redox flow batteries offer promising prospects for large-scale, high-safety, and cost-effective energy storage systems with no reliance on scarce mineral resources. However, challenges such as limited water solubility and poor stability hinder the practical application of organic redox molecules in aqueous organic redox flow batteries. Herein, we report the design and synthesis of an artificial redox-active α-amino acid molecule by functionalizing 1,5-dihydroxyanthraquinone with natural cysteine side group, which exhibits enhanced aqueous solubility and redox reversibility in alkaline aqueous organic redox flow batteries. Owing to its unique zwitterionic structure and abundant hydrogen bonds, the negolyte based on artificial α-amino acid molecule exhibits a very low capacity decay rate of 0.00025% per cycle (equivalent to 0.011% per day) under 1 M electron transfer. Theoretical simulations and spectroscopic analyses underscore the importance of the symmetric distribution and abundant hydrogen-bonding interactions of amphipathic amino acid side chains in enhancing the stability of the anthraquinone redox core and reducing its dimerization, as well as enhancing its water solubility and redox reversibility. This study presents the promising potential of nature-inspired principles in designing electrochemically stable, redox-active organic molecules, contributing to the advancement of large-scale, biocompatible, and sustainable aqueous organic redox flow batteries.